A method for improving the thermal-oxidative stability of thermoset polyimide composites

CN122917366APending Publication Date: 2026-10-16ZHEJIANG LYUKEAN CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510440780.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,陶瓷热障涂层的制造工艺较为复杂,成本较高,且由于其脆性特点,在机械加工和装配过程中容易损坏

Benefits of technology

[0023]本发明通过对由热固性聚酰亚胺树脂溶液与纤维制得的复合材料采用阶梯式降温程序与超声共振相结合的协同处理,降低了复合材料内部的残余应力,使其在高温环境中不容易产生微裂纹,在不改变树脂结构和不给复合材料增加耐高温涂层的情况下,有效提高了复合材料的玻璃化转变温度,在提高复合材料的耐热性能的同时,大幅度提高了复合材料的长期抗热氧稳定性,从而延长了复合材料的使用寿命。相比于现有技术,本发明的方法操作简单便捷、成本低,且本发明的方法通用性高,适用于由不同工艺制备的热固性聚酰亚胺复合材料的长期抗热氧稳定性提升,提高了复合材料应用于航空发动机、航空、航天等高技术领域中的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917366A_ABST
    Figure CN122917366A_ABST
Patent Text Reader

Abstract

The application discloses a method for improving the thermal-oxidative stability of thermosetting polyimide composite materials, and belongs to the technical field of resin composite materials.The method comprises the steps of sequentially performing stepwise temperature reduction and ultrasonic resonance treatment on the thermosetting polyimide composite material after temperature rising.The method combines the stepwise temperature reduction procedure with the ultrasonic resonance treatment to effectively improve the glass transition temperature of the composite material without changing the resin structure and adding a high-temperature-resistant coating to the composite material, thereby improving the thermal resistance of the composite material and greatly improving the long-term thermal-oxidative stability of the composite material, so that the service life of the composite material is prolonged.Compared with the prior art, the method is simple and convenient to operate and low in cost, and the reliability of the composite material in high-tech fields such as aviation and spaceflight is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of resin composite materials technology, and more specifically to a method for improving the thermo-oxidative stability of thermosetting polyimide composite materials. Background Technology

[0002] Thermosetting polyimide composites, due to their superior specific strength and stiffness, excellent designability, and outstanding temperature resistance, have become key materials for replacing medium- and high-temperature metal components to achieve weight reduction, especially in the cold-end sections of aero-engines. As the aerospace industry continues to demand higher material performance, the requirements for aero-engine materials are no longer limited to good high-temperature performance, but also include excellent thermo-oxidative stability and good mechanical properties under long-term high-temperature operating environments to ensure engine safety and reliability.

[0003] However, thermo-oxidative aging is an unavoidable challenge for thermosetting polyimide composites in aero-engine applications. It leads to polyimide decomposition and a decline in the mechanical properties of the composite material, potentially resulting in material failure. Currently, several solutions exist to this problem: On one hand, using polyimide resins with higher temperature resistance can fundamentally solve the thermal aging issue. However, further improving the thermo-oxidative stability of the composite material through the structural design and synthesis of polyimide itself is very difficult and costly. On the other hand, thermal protection measures can be adopted to enhance the heat resistance of the composite material, such as applying low thermal conductivity ceramic thermal barrier coatings. These coatings can isolate heat transfer to a certain extent, reduce the temperature of the composite material, and slow down the thermal aging process. However, the manufacturing process of ceramic thermal barrier coatings is complex and costly, and due to their brittle nature, they are easily damaged during machining and assembly.

[0004] In view of this, it is essential to invent a method that is simple and convenient to operate and can effectively improve the thermo-oxidative stability of thermosetting polyimide composites. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for improving the thermo-oxidative stability of thermosetting polyimide composite materials. The method is simple and convenient to operate, low in cost, can effectively improve the long-term thermo-oxidative stability of composite materials and extend their service life, and has high versatility.

[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the steps of sequentially subjecting the thermosetting polyimide composites to stepwise cooling and ultrasonic resonance treatment after heating.

[0008] In a preferred embodiment of the present invention, the method specifically includes the following steps:

[0009] S1. A thermosetting polyimide resin solution is laminated onto reinforcing fibers, and a prepreg is obtained after removing some of the solvent.

[0010] S2. Place the prepreg obtained in step S1 into a closed mold, apply pressure after stepwise heating, and then maintain the temperature and pressure.

[0011] S3. After the heat preservation is completed, the mold is cooled in stages until it drops below 50°C. The mold is then opened and samples are taken to obtain the composite material. The composite material is then subjected to ultrasonic resonance treatment.

[0012] S4. The composite material obtained in step S3 is subjected to vacuum drying treatment to obtain the final product.

[0013] In a preferred embodiment of the present invention, the thermosetting polyimide in the thermosetting polyimide resin solution in step S1 is a polyimide resin that is end-capped by one of phenylethynyl phthalic anhydride, norbornene phthalic anhydride, or whose main chain structure contains ethynyl bisphthalic anhydride.

[0014] In a preferred embodiment of the present invention, the reinforcing fiber in step S1 is at least one of carbon fiber, quartz fiber, and glass fiber.

[0015] In a preferred embodiment of the present invention, the amount of solvent removed in step S1 is 60-80% of the total amount of solvent.

[0016] In a preferred embodiment of the present invention, after the temperature is raised to 150-350°C in step S2, a pressure of 0.5-5 MPa is applied, and then the temperature and pressure are maintained at 300-400°C and 0.5-5 MPa for 1-24 hours.

[0017] In a preferred embodiment of the present invention, the cooling gradient of the stepped cooling in step S3 is 10 to 80°C, and the cooling time of each gradient is 5 to 30 minutes.

[0018] In a preferred embodiment of the present invention, the ultrasonic medium for ultrasonic resonance treatment in step S3 is one of water, ethanol, methanol, and acetone.

[0019] In a preferred embodiment of the present invention, the ultrasonic frequency of the ultrasonic resonance treatment in step S3 is 0.5-3 MHz and the ultrasonic time is 0.5-10 h.

[0020] In a preferred embodiment of the present invention, the temperature of the vacuum drying process in step S4 is 50-150°C and the drying time is 1-12 hours.

[0021] The present invention also provides a thermosetting polyimide composite material prepared by the above-described method.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] This invention reduces residual stress within the composite material by employing a step-down cooling process combined with ultrasonic resonance to synergistically treat the composite material made from thermosetting polyimide resin solution and fibers. This reduces the likelihood of microcracks forming in high-temperature environments. Without altering the resin structure or adding a high-temperature resistant coating, the glass transition temperature of the composite material is effectively increased. This significantly improves both the heat resistance and long-term thermo-oxidative stability of the composite material, thereby extending its service life. Compared to existing technologies, this method is simple, convenient, and low-cost. Furthermore, it is highly versatile and applicable to improving the long-term thermo-oxidative stability of thermosetting polyimide composite materials prepared using different processes, thus enhancing the reliability of the composite material in high-tech fields such as aerospace, aviation, and aircraft manufacturing. Attached Figure Description

[0024] Figure 1 The image shows a scanning electron microscope (SEM) image of the surface of the thermosetting polyimide composite material prepared in Example 1 of this invention after isothermal thermal oxidation at 300°C for 2000 h.

[0025] Figure 2 The image shows a scanning electron microscope (SEM) image of the surface of the thermosetting polyimide composite material prepared in Comparative Example 1 of this invention after isothermal thermal oxidation at 300°C for 2000 h.

[0026] Figure 3 This is a comparison of the isothermal thermal oxidation weight loss curves at 300℃ for the thermosetting polyimide composite materials prepared in Example 1 and Comparative Example 1 of the present invention. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to specific embodiments.

[0028] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the steps of sequentially subjecting the thermosetting polyimide composites to stepped cooling and ultrasonic resonance treatment after heating. The specific operation includes the following steps:

[0029] S1. A thermosetting polyimide resin solution is applied to reinforcing fibers by impregnation or brushing. After removing 60-80% of the total solvent by drying or natural evaporation, a prepreg is obtained. The thermosetting polyimide in the thermosetting polyimide resin solution is a polyimide resin with one of the following end-capped groups: phenylacetylene phthalic anhydride, norbornene phthalic anhydride, or acetylene phthalic anhydride, or containing acetylene diphthalic anhydride in its main chain structure. The reinforcing fiber is at least one of carbon fiber, quartz fiber, or glass fiber.

[0030] S2. Place the prepreg obtained in step S1 into a closed mold, heat it to 150-350℃ in a stepwise manner, apply a pressure of 0.5-5MPa, and then keep it at 300-400℃ and 0.5-5MPa for 1-24 hours.

[0031] S3. After the heat preservation is completed, the mold is cooled in a step-by-step manner. The cooling gradient of the step-by-step cooling is 10-80℃, and the cooling time of each gradient is 5-30min. After cooling to below 50℃, the mold is opened and samples are taken to obtain the composite material. The composite material is placed in an ultrasonic medium for ultrasonic resonance treatment. The ultrasonic frequency is 0.5-3MHz and the ultrasonic time is 0.5-10h. The ultrasonic medium is one of water, ethanol, methanol, and acetone.

[0032] S4. The composite material obtained in step S3 is subjected to vacuum drying treatment at a temperature of 50-150℃ for 1-12 hours to obtain the final product.

[0033] The present invention will be further described below with reference to specific embodiments and accompanying drawings, but the present invention is not limited to the following embodiments. The thermosetting polyimide resin solutions in the following embodiments were provided by the Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences. The reinforcing fiber in the composite material of the present invention can be at least one of commercially available carbon fiber, quartz fiber, and glass fiber; the following embodiments and comparative examples use carbon fiber as an example.

[0034] Example 1

[0035] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0036] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0037] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0038] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled according to the following cooling program: 300℃ for 10 min, 280℃ for 10 min, 260℃ for 10 min, 230℃ for 10 min, 200℃ for 10 min, 150℃ for 10 min, 100℃ for 10 min, and then naturally cooled to below 50℃ to obtain the composite material; the composite material is placed in an ultrasonic oscillator containing ethanol, the frequency is set to 1MHz, and ultrasonic resonance is performed for 2 hours.

[0039] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0040] Example 2

[0041] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0042] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0043] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0044] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled according to the following cooling program: 280℃ for 10 minutes, 230℃ for 10 minutes, 180℃ for 10 minutes, 120℃ for 10 minutes, and then naturally cooled to below 50℃ to obtain the composite material; the composite material is placed in an ultrasonic oscillator containing ethanol, the frequency is set to 1MHz, and ultrasonic resonance is performed for 2 hours.

[0045] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0046] Example 3

[0047] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0048] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0049] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0050] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled according to the following cooling program: 300℃ for 10 min, 280℃ for 10 min, 260℃ for 10 min, 230℃ for 10 min, 200℃ for 10 min, 150℃ for 10 min, 100℃ for 10 min, and then naturally cooled to below 50℃ to obtain the composite material; the composite material is placed in an ultrasonic oscillator containing ethanol, the frequency is set to 3MHz, and ultrasonic resonance is performed for 1 hour.

[0051] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0052] Example 4

[0053] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0054] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0055] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0056] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled according to the following cooling program: 300℃ for 10 min, 280℃ for 10 min, 260℃ for 10 min, 230℃ for 10 min, 200℃ for 10 min, 150℃ for 10 min, 100℃ for 10 min, and then naturally cooled to below 50℃ to obtain the composite material; the composite material is placed in an ultrasonic oscillator containing ethanol, the frequency is set to 1MHz, and ultrasonic resonance is performed for 2 hours.

[0057] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 150°C for 12 hours to obtain the final product.

[0058] Example 5

[0059] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0060] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0061] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0062] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled down according to the following cooling program: 300℃ for 10 minutes, 280℃ for 10 minutes, 260℃ for 10 minutes, 230℃ for 10 minutes, 200℃ for 10 minutes, 150℃ for 10 minutes, 100℃ for 10 minutes, and then naturally cooled down to below 50℃ to obtain the composite material; the composite material is placed in an ultrasonic oscillator containing acetone, the frequency is set to 1MHz, and ultrasonic resonance is performed for 2 hours.

[0063] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0064] Comparative Example 1

[0065] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0066] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0067] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0068] S3. After the heat preservation is completed, allow the material to cool naturally to below 50°C, then open the mold and take a sample to obtain the composite material.

[0069] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0070] Comparative Example 2

[0071] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0072] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0073] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0074] S3. After the heat preservation is completed, the flat vulcanizing machine is cooled down according to the following cooling program: 300℃ for 10 minutes, 280℃ for 10 minutes, 260℃ for 10 minutes, 230℃ for 10 minutes, 200℃ for 10 minutes, 150℃ for 10 minutes, 100℃ for 10 minutes, and then naturally cooled down to below 50℃ to obtain the composite material.

[0075] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0076] Comparative Example 3

[0077] A method for improving the thermo-oxidative stability of thermosetting polyimide composites includes the following steps:

[0078] S1. Apply the thermosetting polyimide resin solution to the carbon fiber cloth at a mass ratio of resin solution: carbon fiber cloth = 1.4:1. After heating at 80°C to remove about 75% of the total solvent, the prepreg is obtained.

[0079] S2. Cut the prepreg obtained in step S1 according to the mold size and put it into a 200×200mm closed metal mold. Place the mold in a flat vulcanizing machine, first heat it to 150℃ and keep it at that temperature for 1 hour, then heat it to 200℃ and keep it at that temperature for 1 hour, then heat it to 300℃ and keep it at that temperature for 10 minutes. Apply a pressure of 2-3MPa and heat it to 316℃ and keep it at that temperature and pressure for 12 hours.

[0080] S3. After the heat preservation is completed, allow the material to cool naturally to below 50℃, then open the mold and take a sample to obtain the composite material. Place the composite material in an ultrasonic oscillator containing ethanol, set the frequency to 1MHz, and perform ultrasonic resonance for 2 hours.

[0081] S4. After cutting the composite material obtained in step S3, place it in a vacuum oven and dry it at 100°C for 6 hours to obtain the final product.

[0082] I. Performance Testing of Thermosetting Polyimide Composites

[0083] The glass transition temperature and weight loss of the thermosetting polyimide composites prepared in Examples 1-5 and Comparative Examples 1-3 were determined, and the results are shown in Table 1.

[0084] Table 1 Performance testing of thermosetting polyimide composites

[0085] project <![CDATA[Tg a (℃)]]> <![CDATA[Weight loss rate b > <![CDATA[Weight loss rate c > Example 1 391 2.6% 6.1% Example 2 388 2.9% 6.9% Example 3 385 3.5% 7.9% Example 4 389 2.7% 6.3% Example 5 390 2.5% 6.1% Comparative Example 1 380 5.1% 10.9% Comparative Example 2 382 4.6% 9.9% Comparative Example 3 384 4.1% 9.2%

[0086] In Table 1, a represents the glass transition temperature of the composite material, with the temperature at which the loss factor peaks being taken as the reading. b represents the weight loss rate of the composite material after isothermal thermo-oxidative aging at 300℃ for 2000h. c represents the weight loss rate of the composite material after isothermal thermo-oxidative aging at 350℃ for 800h.

[0087] As can be seen from the data in Table 1, the polyimide composites of Examples 1-5 adopted a step-down cooling and ultrasonic resonance synergistic treatment method, which slightly increased their glass transition temperature compared with the composites of Comparative Examples 1-3. This is beneficial for the composites to maintain higher mechanical properties at high temperatures or to be used in higher ambient temperatures. Thermosetting polyimide composites prepared by traditional methods will generate large residual stress inside, while the method of the present invention will significantly reduce the residual stress inside the composites and will not easily generate microcracks in high-temperature environments. The generation of microcracks will increase the surface area of ​​resin in contact with air, resulting in a higher thermal weight loss rate. Therefore, it will have better long-term thermo-oxidative stability than the composites prepared by traditional methods.

[0088] II. Scanning electron microscope images and thermal oxidation weight loss curves

[0089] Scanning electron microscopy (SEM) tests and weight loss curves of the thermosetting polyimide composites prepared in Example 1 and Comparative Example 1 after isothermal thermal oxidation at 300°C for 2000 h were performed. The results are shown in the figure. Figures 1-3 .

[0090] By comparison Figure 1 and Figure 2 It can be seen that, under the same process and drying conditions, the surface composition of the composite material in Comparative Example 1 under scanning electron microscopy shows significantly more severe decomposition than that in Example 1. This is due to... Figure 3 The thermal oxidation weight loss curve also shows that the composite material treated by the method of this invention has better long-term thermal oxidation stability.

[0091] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A method for improving the thermo-oxidative stability of thermosetting polyimide composites, characterized in that: include: The thermosetting polyimide composite material is heated and then subjected to step-by-step cooling and ultrasonic resonance treatment.

2. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 1, characterized in that: Specifically, the following steps are included: S1. A thermosetting polyimide resin solution is laminated onto reinforcing fibers, and a prepreg is obtained after removing some of the solvent. S2. Place the prepreg obtained in step S1 into a closed mold, apply pressure after stepwise heating, and then maintain the temperature and pressure. S3. After the heat preservation is completed, the mold is cooled in stages until it drops below 50°C. The mold is then opened and samples are taken to obtain the composite material. The composite material is then subjected to ultrasonic resonance treatment. S4. The composite material obtained in step S3 is subjected to vacuum drying treatment to obtain the final product.

3. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2, characterized in that: The thermosetting polyimide in the thermosetting polyimide resin solution in step S1 is a polyimide resin that is end-capped by one of phenylethynyl phthalic anhydride, norbornene phthalic anhydride, or whose main chain structure contains ethynyl bisphthalic anhydride.

4. The method for improving the thermo-oxidative stability of thermosetting polyimide composite materials according to claim 2, characterized in that: In step S1, the amount of solvent removed is 60-80% of the total amount of solvent.

5. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2, characterized in that: In step S2, the temperature is gradually increased to 150–350°C, and then a pressure of 0.5–5 MPa is applied. The temperature and pressure are then maintained at 300–400°C for 1–24 hours.

6. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2, characterized in that: The cooling gradient of the stepped cooling in step S3 is 10 to 80°C, and the cooling time for each gradient is 5 to 30 minutes.

7. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2, characterized in that: The ultrasonic medium used in step S3 for ultrasonic resonance treatment is one of water, ethanol, methanol, or acetone.

8. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2 or 7, characterized in that: The ultrasonic frequency of the ultrasonic resonance treatment in step S3 is 0.5-3 MHz and the ultrasonic time is 0.5-10 h.

9. The method for improving the thermo-oxidative stability of thermosetting polyimide composites according to claim 2, characterized in that: The vacuum drying process in step S4 is performed at a temperature of 50–150°C for 1–12 hours.

10. A thermosetting polyimide composite material, characterized in that: It is prepared by the method described in any one of claims 1 to 9.